Chilean Students From Public Educational Institutions With Poor Sleep Hygiene Exhibit Lower Self-Esteem. Cross-Sectional Study - Ibarra-Mora, Jessica; Cigarroa, Igor; Zapata-Lamana, Rafael; Hernández-Mosqueira, Claudio; Reyes-Amigo, Tomás; Maureira-Cid, Fernando (Revista Electrónica Educare, 2024)
Objective. To analyze the self-esteem of Chilean students from public schools and determine its association with sleep hygiene variables, after the first year of restrictions due to the COVID-19 pandemic. Method. The study had a non-experimental, descriptive, and analytical design, with a cross-sectional temporal dimension. A convenience non-probabilistic sample of 265 students from 7th to 12th grade (between 11 and 18 years old) of both sexes from the town of El Carmen, southern Chile, participated in an online questionnaire about context, self-esteem, and sleep habits. Analysis of results. A majority of students perceived themselves with average or low self-esteem (26.4% and 24.9%, respectively). It was found that students who usually fell asleep before midnight, did not wake up tired or did so occasionally, did not have nightmares, and did not usually have trouble falling asleep had higher self-esteem than those who fell asleep after midnight, woke up tired regularly, had nightmares, and had trouble falling asleep, respectively. Conclusions. It was concluded that a high percentage of students had average or low self-esteem, and that students who reported having better sleep hygiene had higher self-esteem compared to those who had worse sleep hygiene. In this way, further studies are necessary to address these topics, especially in contexts of uncertainty, where it is presumed that they could have an impact on both lifestyle habits and mental health.